2013
DOI: 10.1021/co400080z
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic, Acidic, Ionic Liquid-Catalyzed One-Pot Synthesis of Spirooxindoles

Abstract: Magnetic, supported, acidic ionic liquid was synthesized and identified as an efficient catalyst for the one-pot synthesis of novel spirooxindole derivatives at mild conditions and in good yields. Three component reaction of wide variety of substituted isatins, 1,3-dimethyl-2-amino uracil, and barbituric acid, thiobarbituric acid, and dimedon as 1,3-dicarbonyl compounds gives the target compounds. Operational simplicity, low cost, high yields, environmental friendliness, wide applicability and reusability and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 47 publications
0
38
0
Order By: Relevance
“…Interestingly, a diverse range of substrates underwent a smooth transformation and the desired spirooxindole products were obtained in good to excellent yields (Table ). It was found, in the presence of the Fe 3 O 4 /GO/Au‐Ag nanocomposite as a catalyst, the reaction times and yields of some spirooxindole derivatives were improved in comparison with the previous report at the same solvent and temperature …”
Section: Resultsmentioning
confidence: 58%
“…Interestingly, a diverse range of substrates underwent a smooth transformation and the desired spirooxindole products were obtained in good to excellent yields (Table ). It was found, in the presence of the Fe 3 O 4 /GO/Au‐Ag nanocomposite as a catalyst, the reaction times and yields of some spirooxindole derivatives were improved in comparison with the previous report at the same solvent and temperature …”
Section: Resultsmentioning
confidence: 58%
“…In another research, Khalafi-Nezhad and Mohammadi [62] reported a magnetic-supported acidic ionic liquidcatalyzed one-pot synthesis of spirooxindoles. Operational simplicity, low cost, high yields, wide applicability Also, Abu-Reziq et al [63] found that the Pt nanoparticles immobilized on MNPs modified with ionic liquids (ILs) are very efficient and reusable catalyst for the chemoselective hydrogenation of α,β-unsaturated aldehydes and alkynes.…”
Section: Ionic Liquids Immobilized On Magnetic Nanoparticlesmentioning
confidence: 99%
“…MCRs combine from three up to eight reactants to furnish products containing structure or substructure of all starting materials in one pot, that offers significant advantages in normal linear synthesis because of its convergent, flexible, atom efficient nature and reducing the number of purification steps . Over the past decade, considerable attention has been focused on the development of new methodologies to MCRs, especially applicability of nanocatalysts in MCRs . Among the wide varieties of MCRs, the synthesis of benzodiazepine is a reaction of three component that is considered a privileged scaffold in medicinal chemistry, bioactive natural products and many biologically active compounds bear this core …”
Section: Introductionmentioning
confidence: 99%